Sistem Administrasi Pada Toko Eye's Collection - Suteja, Steven; Rostianingsih, Silvia; Triyono, Dedy (Jurnal Infra, 2018)
Eye's Collection Store is engaged in women's fashion that is selling women's clothing including blouse, sackdress, leggings, jeans, and others. So far, listing on the Eye's Collection Store begins sales, purchases, and purchase returns are recorded manually so that owners experience difficulty in recording transaction data.The result of this application development is able to search and recording sales transactions, purchases, purchase returns, supplier data, inventory, and customer data. Eye's Collection Store owners can also view important reports such as purchases, sales and purchase returns. Based on the results of questionnaires were obtained for display applications, 66,6% of respondents answered good, and 33,3% of respondents answered very well. For ease of use, 66,6% of respondents answered good, and 33,3% of respondents answered very well. For completeness of information, 33,3% of respondents answered enough, 33,3% of respondents answered good and 33,3% of respondents answered very well. For compliance with requirements, 33,3% of respondents answered good, and 66,6% of respondents answered very well. For report results, 33,3 % of respondents answered enough, and 66,6% of respondents answered good and. For most applications, 33,3% of respondents rate the program was good, and 66,6% of respondents rate the program is very good.